Nutrient load inputs to the Cache la Poudre River watersheds - Son, Ji-Hee, author; Carlson, Kenneth H., advisor; Watson, Chester, committee member; Bond, Craig, committee member; Sharvelle, Sybil, committee member (Colorado State University. Libraries, 2013)
Nutrient (phosphorus and nitrogen) has been ranked as a leading source of water quality impairment of surface waters in the United States for the past two decades. Based on strong encouragement for developing in-stream nutrient numeric criteria by the Environmental Protection Agency of the U.S., the Colorado Department of Public Health and Environment proposed the in-stream numeric total phosphorus (TP) and total nitrogen (TN) criteria as 2 mg TN L-1 and 0.16 mg TP L-1 for warm surface waters and 0.40 mg TN L-1 and 0.11 mg TP L-1 for cold surface waters. As a consequence, nutrient limits for point sources, the municipal wastewater treatment plants, have been proposed as annual averages of 0.7 mg TP L-1 and 5.7 mg total inorganic nitrogen (TIN) L-1 and quarterly averages of 1.0 mg TP L-1 and 9.0 mg TIN L-1 to achieve the in-stream standards. Rivers and streams, however, receive nutrient loads from point sources and nonpoint sources in a mixed land-use area and therefore nutrient reduction only at point sources is unlikely to result in improvements to the environment without nonpoint source controls. The objectives of this study were to monitor TP (Chapter 4.1) and TN (Chapter 4.2) concentrations and estimate loads along the Cache La Poudre River as it flows from the pristine upstream area through a mixture of agricultural and urban land uses, and compare the loads between point sources and nonpoint sources under various hydrologic conditions. Twelve and seven sampling events were completed between April 2010 and August 2011 for TP and TN, respectively. Point sources, wastewater treatment plants (WWTPs) in the study area, were the major sources of TP and TN during midrange and dry flow conditions, but nonpoint sources were more substantial under high flow conditions. Loading exceedance of TP from the proposed in-stream TP limit was observed for all hydrologic conditions, but the significance of the exceedance was drastically increased during high flow conditions (p<0.05). Contrary to expectations, significant loading exceedance of TN was observed only for lower flow conditions, and other sources dominated during events when exceedance of TN was observed. Nutrient loads increased in areas of greater anthropogenic influence (p < 0.05) and nonpoint source loads became significant in the areas with more agricultural activity (p < 0.05). We attempted to simulate TP and TN loads in the CLP River to determine whether the loads under different effluent conditions in the WWTPs would comply with the proposed in-stream limits (Chapter 4.3). The study shows that reducing nutrient load only at WWTPs will merely reduce nutrient load in the river and that the in-stream limits cannot be achieved without substantial reduction of nonpoint source loads (e.g., stormwater and agricultural runoff) and therefore other sources need to be considered in establishing the in-stream standard limits. An intense wildfire occurred in a forested area of Colorado in June 2012 while a study of the role of riverbed sediment in terms of phosphorus source under various hydrologic conditions was being conducted. River water and sediment samples were collected after the fire, and water quality and sediment properties of the post-fire samples were spatially and temporally compared with the pre-fire samples collected prior to the fire event (Chapter 4.4). Disturbance of water quality and soil properties by the fire were observed, but the magnitude of significance was relatively small without precipitation; however, in-stream TN and TP concentrations significantly increased in the upstream section after precipitation event. Large amounts of particulate P were introduced to the upstream section and impacts downstream were apparent. After precipitation event, soluble reactive phosphorus (SRP) dominated dissolved P in the river replacing dissolved organic phosphorus (DOP), which was the main dissolved species before the fire event. In the riverbank, TP mass concentration increased significantly after fire with silt-clay and organic matter (OM) concentrations after precipitation. Riverbed TP mass concentrations decreased due to a reduced sorption capacity leading to a considerable P release from the sediments. The results indicate that fire-released P species will impact the downstream area of the watershed for a considerable time period as the bank erosion-sorption-desorption cycles in the watershed adjust to the fire-related loading.
Keywords: nutrient; wildfire; riverbed sediment; Cache la Poudre River; nonpoint source; WWTP